Searching for evidence of interaction between the of star HD 229196 and the interstellar medium - Pineault, Serge (2008)
Massive stars with strong stellar winds are expected to have a huge impact on their interstellar surroundings, an effect which, in a surprisingly large number of cases, is not observed. This work is part of a concerted effort to obtain a better and more homogeneous observational data base with which to test the predictions of theoretical models. Analysis of the interstellar medium around the Of star HD 229196 shows that it coincides (in projection) with a region of lower radio continuum emission. This suggests that the star has shaped the surrounding interstellar medium via its ionizing flux and stellar wind. However, we find no clear evidence of the star's action in atomic hydrogen images. The radio continuum morphology and absence of a clear expanding H i shell are consistent with the possibility that the star, which is travelling supersonically at ∼30 km s-1 with respect to its local interstellar medium, is creating a weak bow shock. We cannot however rule out the possibility that the observed asymmetry is due to an inhomogeneous interstellar density distribution. We use data from the Canadian Galactic Plane Survey to carry out this study.